The cellular economy of the Saccharomyces cerevisiae zinc proteome. Issue 12 (25th October 2018) - Wang, Yirong; Weisenhorn, Erin; MacDiarmid, Colin W.; Andreini, Claudia; Bucci, Michael; Taggart, Janet; Banci, Lucia; Russell, Jason; Coon, Joshua J.; Eide, David J.
Abstract : We cataloged the zinc proteome of Saccharomyces cerevisiae and analyzed how it responds to changing zinc status. Abstract : Zinc is an essential cofactor for many proteins. A key mechanism of zinc homeostasis during deficiency is "zinc sparing" in which specific zinc-binding proteins are repressed to reduce the cellular requirement. In this report, we evaluated zinc sparing across the zinc proteome of Saccharomyces cerevisiae . The yeast zinc proteome of 582 known or potential zinc-binding proteins was identified using a bioinformatics analysis that combined global domain searches with local motif searches. Protein abundance was determined by mass spectrometry. In zinc-replete cells, we detected over 2500 proteins among which 229 were zinc proteins. Based on copy number estimates and binding stoichiometries, a replete cell contains ∼9 million zinc-binding sites on proteins. During zinc deficiency, many zinc proteins decreased in abundance and the zinc-binding requirement decreased to ∼5 million zinc atoms per cell. Many of these effects were due at least in part to changes in mRNA levels rather than simply protein degradation. Measurements of cellular zinc content showed that the level of zinc atoms per cell dropped from over 20 million in replete cells to only 1.7 million in deficient cells. These results confirmed the ability of replete cells to store excess zinc and suggested that the majority of zinc-binding sites on proteins in deficient cells are either unmetalated or mismetalated. Our analysis of two abundant zinc proteins, Fba1 aldolase and Met6 methionine synthetase, supported that hypothesis. Thus, we have discovered widespread zinc sparing mechanisms and obtained evidence of a high accumulation of zinc proteins that lack their cofactor during deficiency.